(3CbSGe Gdehdis - (3GdYcHQj, GdMGQKj, GdHZOGOj, GdcQNj, CHh YHO Gddg, GdTjN GdoepajO, eMeO Hf eMeO Hf GdfYeGf Hf YHO GdSdGe, J (B413s ((3SQ ef QCis)
(3ChdgG (B:s
(3eNJUQ GdcdGe aj CbSGe Gdehdi aj GddSGf(B...(3CeG HYO(B...(3aEfj eeJKd eG QSeg ef EKHGJ CbSGe Gdehdi aj GddSGf hPcQ WQa ef GdGSJOdGd Ydi EeGeI CejQ GdeDfjf Ydj(B...s
(3BNQgG (B:s
(3aUM eG CKHJfG ef gPg GdCTYGQ dhdGFgeG Ydi eG PcQfG ef HQgGf QShd Gddg(B...s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B:(3L(B7(3,U(B21s
(3GdPQjYI(B:(3L(B2(3,U(B154(3,Qbe(B1101s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds